Iconography of Peace Сongresses during the Formation of the Westphallian System - Ivonina, Liudmila (Eikón / Imago, 2021)
The formation of the first state system in Europe took place from the conclusion of the Peace of Westphalia in 1648, as a result of the Thirty Years’ War (1618-1648), to the Utrecht (1713), Rastatt-Baden (1714) and Nystad Congresses (1721) which finished the end of the war of the Spanish Succession and the Northern war. The legal fixation of the Westphallian system was accompanied by its public perception and acceptance. First of all, this was demonstrated by International Congresses, which were not only a common negotiation process, but also a place of representation of the significance and culture of each state. In fact, the European Congress was a carefully designed triumph of Рeace within the continent, which required considerable funds, was widely covered in the press and glorified in celebrations, paintings, plastic art, release of commemorative medals, poetry and even fashion. The article presents the most striking examples of iconography of Peace Congresses. The author believes that their performative nature and iconography, emphasizing the European character of Peace and the protopatriotic moods that it evoked, made a significant contribution to the civilization heritage of Europe.